Near-Infrared Light-Triggered Photodynamic Therapy and Apoptosis Using Upconversion Nanoparticles With Dual Photosensitizers - Lee, Song Yeul; Lee, Ruda; Kim, Eunha; Lee, Sanghee; Park, Yong Il (Frontiers in Bioengineering and Biotechnology, 2020)
Upconversion nanoparticles (UCNPs), which can be excited by near-infrared (NIR) light, are attractive in the field of photodynamic therapy (PDT). However, the PDT efficiency of conventional UCNPs is limited due to low quantum yield and the overheating effect of the 980 nm light source. Here, we synthesized NaYF4:Yb,Er,Nd@NaYF4:Yb,Nd UCNPs with dual photosensitizers. We used 808 nm as an excitation source of Nd-doped UCNPs to solve the overheating effect, and synthesized the UCNPs with core@shell structure to increase the upconversion emission efficiency. We also utilized the dual-color emitting Er-doped UCNPs and dual photosensitizers (Chlorin e6 and Rose Bengal) for enhanced PDT. Each of the photosensitizers can absorb red and green emissions of the UCNPs to generate reactive oxygen species (ROS), respectively. ROS generation in a dual photosensitizer system was much higher than the ROS generation in a single photosensitizer system. In addition, PDT induces immunogenic apoptosis. Using a highly efficient PDT agent, PDT-induced apoptosis was also studied for potential cancer immunotherapy.